2014
DOI: 10.3194/1935-8156-9.1.24
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Accounting Information Systems in the Accounting Curricula: A CPA Perspective

Abstract: Research regarding accounting program curricula design has been extensive. While attention has been given to generic skills, the relative importance of specific functional skills has been lacking. The importance of accounting information systems (AIS) knowledge and skills has been assumed but rarely tested although it is an integral part of most accounting programs. Little attention has been given to the comparative value of AIS topics within the overall accounting curricula. In this study, 56 CPAs were survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…This study, like previous research, finds that three IT skills continue to be in the top five rankings regardless of whether or not firm size is a consideration:  spreadsheets (Dillon & Kruck, 2008;Chen et al, 2009;Welch et al, 2010;Cory & Pruske, 2012;Kearns, 2014;Lee et al, 2018)  Word Processing (Chen et al, 2009;Welch et al, 2010;Cory & Pruske, 2012)  Internet research (Welch et al, 2010;Cory & Pruske, 2012). This research's results also support previous findings that firm size is not a factor for Cloud Computing (Gupta et al, 2013;Seethamraju, 2015;Loukis et al, 2017).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This study, like previous research, finds that three IT skills continue to be in the top five rankings regardless of whether or not firm size is a consideration:  spreadsheets (Dillon & Kruck, 2008;Chen et al, 2009;Welch et al, 2010;Cory & Pruske, 2012;Kearns, 2014;Lee et al, 2018)  Word Processing (Chen et al, 2009;Welch et al, 2010;Cory & Pruske, 2012)  Internet research (Welch et al, 2010;Cory & Pruske, 2012). This research's results also support previous findings that firm size is not a factor for Cloud Computing (Gupta et al, 2013;Seethamraju, 2015;Loukis et al, 2017).…”
Section: Discussionsupporting
confidence: 77%
“…Software, and Database Software. A later study (Kearns, 2014), surveying CPAs reveals the following ranking of eight IT skills: Spreadsheet Tools, Governance/Internal Controls, Database Tools, fraud detection and prevention, Computer Networks, IT Security, XBRL, and Audit Software Tools. Winstead and Wenger's (2015) survey of academicians and practicing accountants indicates both groups agree on the importance of operating systems, Software Packages, and Report Software, while practitioners feel Business Cycles, Data Sharing, XBRL, Problem Solving Technology, E-Commerce, and safeguarding electronic accounting records are less important.…”
Section: Textbooks and Syllabimentioning
confidence: 99%
“…Survey method was used as a data collection tool in the research. The questionnaire was developed by Kearns (2014). However, the skills included in the survey, were revised in the framework of accounting education in Turkey.…”
Section: Methodsmentioning
confidence: 99%
“…Smith and Bain (1993) found that internal control and associated systems are the most important topics covered in AIS courses in the eyes of AIS faculty. More recently, Kearns (2014) confirmed that AIS knowledge is recognized by certified public accountants (CPAs). In Kearns's study (2014), surveyed CPAs considered spreadsheet tool is the most important whereas audit software and tool is the least important topic in AIS.…”
Section: Introductionmentioning
confidence: 73%